Combined Lumbar Plexus and Sciatic Nerve Blocks Improve Postoperative Recovery in Lower Extremity Surgery: A Randomized Controlled Trial - Wiranata, Jeremia Alvian; Aribawa, I Gusti Ngurah Mahaalit; Parami, Pontisomaya; Senapathi, Tjokorda Gde Agung; Hartawan, I Gusti Agung Gede Utara; Adi, Made Septyana Parama; Kurniajaya, I Gusti Agung Made Wibisana; Pradhana, Adinda Putra (Faculty of Medicine, Brawijaya University, 2026)
Background: Patients undergoing lower extremity orthopedic surgery often experience moderate to severe postoperative pain, commonly managed with opioids. Regional anesthesia techniques, such as peripheral nerve blocks, offer promising alternatives. This study evaluates the efficacy of combined lumbar plexus block (LPB) and sciatic nerve block (SNB) versus intravenous opioid analgesia in enhancing postoperative recovery and pain control. Methods: In a single-blind, randomized controlled trial, 42 patients scheduled for lower extremity orthopedic surgery under spinal anesthesia were allocated to two groups. Group P1 received postoperative LPB and SNB using 20 mL of 0.25% bupivacaine, while group P2 received intravenous opioids. Outcomes at 24 hours included quality of recovery (QoR-40) scores, total morphine consumption, duration of analgesia, and monitored adverse events. Result: Group P1 showed significantly better recovery scores [QoR-40: 183 (178–188) vs. 152 (136–161.5), p < 0.001], reduced morphine consumption [4 (4–6.5) mg vs. 18 (16–22) mg, p < 0.001], and longer analgesia duration [480 (340–600) min vs. 75 (60–110) min, p < 0.001]. No adverse events were observed. Conclusion: Combined LPB and SNB significantly improve postoperative recovery quality and analgesia in patients undergoing lower extremity orthopedic surgery, reducing opioid requirements and extending pain-free duration compared to intravenous opioids.